“Letting Go” (Implicitly): Priming Mindfulness Mitigates the Effects of a Moderate Social Stressor - Bergeron, Catherine M.; Almgren-Doré, Isabelle; Dandeneau, Stéphane (Frontiers in Psychology, 2016)
This experimental study investigated whether implicitly priming mindfulness would facilitate psychological and cortisol recovery after undergoing a standardized psychological stressor. After completing baseline measures of wellbeing, all participants (N=91) completed a public speaking stress task, were implicitly primed with “mindfulness” or “neutral” concepts using a scrambled sentence task, and finally, reported their situational wellbeing and provided cortisol samples. Simple moderation regression analyses revealed that the implicit mindfulness condition had significant beneficial effects for participants with low trait mindfulness. These participants reported higher situational self-esteem as well as less negative affect, perceived stress, and self-reported physiological arousal than their counterparts in the control condition. Cortisol analyses revealed that participants in the implicit mindfulness condition, regardless of level of trait mindfulness, showed a greater decline in cortisol during the early recovery stage compared to those in the control condition. Overall, results suggest that implicitly activating mindfulness can mitigate the psychological and physiological effects of a social stressor.